Individual Characteristics And Discipline Of Performance - Lailatur Rizki, Via (Jurnal Ilmu Manajemen Advantage, 2020)
This article analyze the individual characteristics and police work discipline on the performance of traffic police. Lumajang. This article used a quantitative approach and the testing of hypotheses, a population that is used is the police of traffic police, Lumajangthe sample collection and use of census. The method of analysis of the data used in the article it is multiple regression analysis. The result showed that significant individual characteristics have a positive impact on the performance of traffic police precinct Lumajang. Work discipline have a positive impact on the performance of traffic police precinctLumajang.